Fatigue Among Nursing Students During COVID-19 Pandemic in Medan - Tinambunan, Hotria Veronika; Tumanggor, Roxsana Devi (Talenta Publisher, 2022)
The COVID-19 pandemic requires students to implement an online learning system. However, the online learning method will be effective if it is supported by a systematically stable network. Online learning stimulates several problems related to physical and psychological issues. This study aims to describe nursing students’ fatigue during online learning at the Faculty of Nursing, University of Sumatera Utara. This study is a descriptive study with a sample of 87 respondents, which were taken using the proportionate stratified random sampling technique. The research instrument used in this study consisted of two parts, namely demographic data and Chalder fatigue instruments. Data collection is conducted through online with google forms link via WhatsApp group. The prospective samples were fill the agreement to participate in the survey and research link was send directly. Data analysis was conducted to determine the frequency distribution of the variables studied. The results showed that the majority of the samples were female (89.7%), aged 20-22 years (69.4%). For the fatigue level, the data showed that most students were in the range of moderate levels of fatigue (52.2%). And, there are 2 students (2.3%) who are in severe fatigue range. Based on the results of this study, it is hoped that it can become basic data for further research that can provide a more in-depth analysis of the fatigue contributed factors among students during online learning with pandemic COVID-19 affect.